Job satisfaction and turnover intentions among health care staff providing services for prevention of mother-to-child transmission of HIV in Dar es Salaam, Tanzania - Naburi, Helga; Bärnighausen, Till (Human resources for health, 2017)
Option B+ for the prevention of mother-to-child transmission (PMTCT) of HIV (i.e., lifelong antiretroviral treatment for all pregnant and breastfeeding mothers living with HIV) was initiated in Tanzania in 2013. While there is evidence that this policy has benefits for the health of the mother and the child, Option B+ may also increase the workload for health care providers in resource-constrained settings, possibly leading to job dissatisfaction and unwanted workforce turnover.